Causes of different force-velocity relationships in sprint running depending on horizontal loads and profiling methods - Sugisaki, N; Tsuchie, H; Takai, Y; Kobayashi, K; Yoshimoto, T; Kanehisa, H. (Medicine & Science in Sports & Exercise, 2025)
Purpose We aimed to clarify how the horizontal force-velocity (Fvh) relationship during over-ground sprint running differs with horizontal resistance loads and profiling methods (multiple- and single-trial methods).